(untitled) (Legal journal - Research in Legal and Social Sciences, 2023)
This paper seeks to analyze the confidential nature of the financial intelligence reports issued by the Seprelad, by means of analyzing current legislation that enables pragmatic alternatives for enforcing the law and to bond it with constitutional normative that insures the safeguard of the criminal investigation. In this context, the reports are used in money laundering cases. Accordingly, the criminal investigation begins in two ways: 1) when it is interrelated with other investigations of criminal nature such as: drug trafficking, smuggling, trafficking in humans, fraud, usury, etc, and; 2) following a financial intelligence report provided by Seprelad’s Financial Intelligence Unit. Regarding this point, the Public Ministry does not include the mentioned report as background information for opening a criminal investigation, in accordance with the article 22 of the Act number 6.497/19 that establishes that the reports and all submitted information are privileged and shall only be used within the framework of this Act. This research covers this legal stipulation by considering the eventual limitation of the exercise of the defendant’s legal defense, and also the risk of Public Ministry’s prosecution due to eventual request for annulment of charges, because of the confrontation with constitutional normative. To this effect, the methodology applied is the documentary analysis of descriptive type.